Impact of COVID-19 on Global Container Shipping Industry - Danelia, Irakli (European Scientific Journal, ESJ, 2021)
This paper demonstrates the Global economic outlook resulted by COVID-19 pandemic and provides an analysis of the direct and indirect impact on Global Container shipping industry. It also discussed sequential interdependence among Pandemic, Global Economic downturn, and Challenges in Global Containerized cargo flows. The paper analysis actual results and the features of the economic crisis caused by COVID-19 pandemic on Global Container shipping industry. While Identifying key determinants of accelerating challenges for Containerized Cargo flows during the global pandemic, the paper concludes short and long terms expectations that might be defined for Future development in the global container Shipping industry.